A multiple case study on clothing-related needs of selected bedridden patients in Metro Manila - Mariano, Jilleanne M.
Despite advancements in clothing solutions, health risks and stresses faced by bedridden patients and their caregivers persist. Therefore, understanding their needs is crucial. This study aimed to analyze the clothing-related needs of selected adult bedridden patients in Metro Manila. Specifically, the study investigated their daily activities and clothing-related challenges, clothing solutions utilized by their caregiver, and the patient’s level of satisfaction with the solutions in terms of Functional, Expressive, Aesthetic, and Accessibility considerations. Four patients were conveniently selected as cases for the study. The data collected were from their caregiver’s perspective and were thematically analyzed. Aside from basic activities like eating and dressing, the patients’ other daily activities depended on their medical treatments, ability to go outside, and their caregivers’ choices. Moreover, most of their challenges were under Functional considerations, like difficulty in dressing due to the garment’s fit and type of closure. Their clothing solutions were necessity- driven and prioritized comfort, ease of wear, and protection. According to the caregivers, the patients gave the most importance to Functional considerations and the least to Aesthetic considerations. Although their satisfaction levels were favorable overall, they were dissatisfied with some specific attributes under the four considerations. For example, under Aesthetic, one was dissatisfied with the style, color, and attractiveness of their hospital gown. Clothing solutions with features that cater to their specific needs, like garments that accommodate medical devices and stylish hospital gowns, would be beneficial to the patients. It is recommended that future studies take into account both the caregiver and patient perspectives to gain a comprehensive understanding of the patient’s situation.